Implementasi Supervisi Klinis untuk Meningkatkan Efektivitas Pembelajaran di MI Nurul Huda - Tuhfatul Widad; Shobihatul Fitroh Noviyanti; Lailatul Masrufa; Muhammad Zaidan Atha'illah (Al-Kindi, 2026)
This research was conducted with the aim of finding out how the implementation of clinical supervision can improve the effectiveness of learning at MI Nurul Huda. The research focuses on the practices and approaches of clinical supervision, the functions and obstacles of supervision, as well as the evaluation of the effectiveness of clinical supervision in improving the quality of teacher learning. This study uses a descriptive qualitative approach involving the principal, teachers, and students as research informants. Data collection techniques use interviews, observations, and documentation. The results of the study show that the implementation of clinical supervision at MI Nurul Huda has been going quite well and is carried out in a structured manner, starting from the pre-supervision stage, the implementation of supervision, and follow-up post-supervision. This clinical supervision also functions as a form of fostering teacher professionalism in improving the quality of learning. By using a clinical and collaborative approach, teachers feel comfortable and helped in improving the teaching process. Nevertheless, the implementation of clinical supervision still faces some obstacles such as limited time for implementation, changes in the supervision schedule, and limited teaching media. However, in general, clinical supervision has a positive impact on improving teacher professionalism and the effectiveness of learning at MI Nurul Huda.